Understanding Virtual Objects through Reverse Engineering - Vera Moitinho; Juan Anton Barceló (Virtual Archaeology Review)
The main objective of our research is to develop a new methodology, based on Reverse Engineering processes – 3D scan, quantitative data analysis and Artificial Intelligence techniques, in particular simulation – to study the relationship between form and function of artefacts. Furthermore, we aim to provide new data, as well as possible explanations of the archaeological record according to what it expects about social activity, including working processes, by simulating the potentialities of such actions in terms of input-output relationships.